Patient Safety Culture Based on Empowerment Structure with Employee Job Satisfaction at Abdoel Wahab Sjahranie Samarinda Hospital - Puspitasari, Dwi Ida; Suwanto, Suwanto; Supriyatno, Andik; Aidillah, Muhammad Rafli; Gunawan, Muhammad Henry; Hartati, Dwi; Oktaviyanti, Wahyu; Sirait, Yusnita; Jumrana, Jumrana; Supardi, Supardi (Chakra Brahmanda Lentera Institute, 2026)
Background: Patient safety culture and structural empowerment are organizational factors that play an important role in improving the quality of service and job satisfaction of hospital employees. Although the relationship between the two variables has been extensively researched, empirical evidence examining their effect simultaneously on job satisfaction at referral hospitals in Indonesia is still limited. This study aims to analyze the relationship between patient safety culture and structural empowerment with employee job satisfaction at Abdoel Wahab Sjahranie Samarinda Hospital. Methods: This study is a quantitative research with a cross-sectional analytical design. The number of samples was 232 hospital employees with proportional sampling procedures from various service units. Patient safety culture was measured using the Hospital Survey on Patient Safety Culture (HSOPSC), structural empowerment using the Conditions of Work Effectiveness Questionnaire-II (CWEQ-II), and job satisfaction using the McCloskey/Mueller Satisfaction Scale (MMSS). Data analysis was carried out descriptively and bivariately using Pearson correlation analysis with a significance level of 5% using SPSS software. Results: There was a positive relationship between patient safety culture and employee job satisfaction (r = 0.675; p < 0.001). Structural empowerment had a significant positive relationship with employee job satisfaction (r = 0.821; p < 0.001). The correlation coefficient value shows that structural empowerment has a stronger relationship with job satisfaction than patient safety culture. Conclusion: Patient safety culture and structural empowerment are significantly related to employee job satisfaction. Strengthening a culture of patient safety, supportive leadership, and increased access to information, resources, support, and professional development opportunities needs to be a hospital management strategy to improve job satisfaction and service quality.